Sistem Pemantauan Parkir Liar Menggunakan Sensor Infrared Berbasis Android (Studi Kasus Politeknik Negeri Malang) - Nur Ahmad Wasian; Mila Kusumawardani; Ridho Hendra Yoga Perdana (Politeknik Negeri Malang, 2021)
Illegal parking in Malang State Polytechnic is still not well monitored. The Officer Pengamanan Dalam(Pamdal), whose job is to curb Polinema residents who park their vehicles, cannot monitor the vehicles regularly, so there are still many who park illegally. Based on this, an automatic system that can be used by Pamdal to monitor illegal parking in Polinema is needed. Therefore,